A Survey of Algorithms Used for the Prevention of Fake Profiles in Social Networks - Dandwani, Manish; Vaibhav, Vishal; Nagadevi, S (International Journal of Engineering and Technology, 2018)
A great many dynamic clients all around the globe are utilizing on the web informal community, for example, Facebook, Twitter, Tumbler and LinkedIn. These shortcomings make it easy to abuse client's data and do personality cloning assault to frame counterfeit profile. In this proposed framework, information concealing systems to shroud some data in profile pictures with a specific end goal to identify botnets and counterfeit profiles. This venture introduces an order and examination of discovery instruments of clone attacks on online interpersonal organization, in light of trait similitude, companion arrange closeness, and profile investigation for a period interim and record of Internet Protocol groupings. In this task we have proposed discrete wavelet change calculation for information covering up. In this manner this would keep the clone assaults and giving complete client information protection saving. Likewise when clients transfer the profile pictures they can be watermarked and refreshed. For the watermarking method Java static watermark can be used. Any phony clients refreshing a similar profile picture can be distinguished and their separate IP would be followed and blocked. Likewise for secure picture transmission, we utilized Discrete Wavelet Transform (DWT) for information concealing/steganography and Discrete Cosine Transform (DCT) for picture pressure.Â Â